Analysis of Family Support in Enhancing Life Quality among Breast Cancer Patients at Haji Adam Malik Central General Hospital Medan - Maulidia Rahima Utami; Sri Rahayu Sanusi; Rahayu Lubis (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
Cancer is the most common chronic disease worldwide, with cervical cancer, breast cancer, ovarian cancer, and skin cancer being the most prevalent. Breast cancer ranks second globally after lung cancer. Patients diagnosed with breast cancer undergo changes in their physical, sexual, social, and daily life activities, affecting their overall life quality. One crucial factor that can enhance the life quality for patients is the support from their families, which is a pivotal determinant for individual well-being. To determine the differences in the life quality among breast cancer patients with high and low family support and to analyze the correlation between family support and the breast cancer patients life quality. This study employed a quantitative analytic survey with a cross-sectional design. The research was conducted at Haji Adam Malik Central General Hospital from August to October 2023. The study population included all stage I and II breast cancer patients, totaling 205 outpatient individuals from March to April 2022, with a sample size of 66. Simple random sampling was utilized for participant selection. Data collection involved questionnaire interviews. Data analysis comprised two steps: first, univariate analysis using descriptive and frequency statistics, and second, bivariate analysis using Pearson's test and independent t-test with a significance level of 95% (p-value ≤ 0.05). Statistical results indicated a significant difference in the life quality between breast cancer patients with high and low family support (p=0.037). It was concluded that there is a significantive correlation between family support and the breast cancer patients life quality (p=0.001; r=-0.644). Family support is crucial for patients facing chronic diseases such as breast cancer. It is recommended that families strive to enhance their support to ensure patients' comfort during treatment and therapy programs, ultimately improving the breast cancer patients life quality. Keyword: Breast Cancer, Family, Life Quality